ICT, skills, and organisational change: Evidence from a panel of Italian manufacturing firms - Paola Giuri; Salvatore Torrisi; Natalia Zinovyeva (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2005)
This paper explores how firms' skills and organizational change affect the returns from investments in ICT. Our work contributes to the literature by testing the hypothesis of complementarity in a panel of 540 Italian manufacturing firms during 1995-2000. By drawing on different statistical methods, we do not find any clearcut support to the hypothesis of full complementarity among ICT, human capital and organizational change. We find a strong support to the hypotheses of skill-biased technical change and a weaker support to the skill-biased organizational change hypothesis particularly in medium-sized firms. Our findings suggest that the productivity gains from investments in the three innovative activities are related to firm size.
Keywords: O30; D24; L23; 330; organizational change; ICT investment; skills; human capital; productivity; complementarity; SMEs; Organisatorischer Wandel; Informationstechnik; Technischer Fortschritt; Humankapital; Produktivität; Industrie; Italien